2021
DOI: 10.48550/arxiv.2110.02767
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Schwarz type lemmas and their applications in Banach spaces

Abstract: The main purpose of this paper is to develop some methods to investigate the Schwarz type lemmas of holomorphic mappings and pluriharmonic mappings in Banach spaces. Initially, we extend the classical Schwarz lemmas of holomorphic mappings to Banach spaces, and then we apply these extensions to establish a sharp Bloch type theorem for pluriharmonic mappings on homogeneous unit balls of C n and to obtain some sharp boundary Schwarz type lemmas for holomorphic mappings in Banach spaces. Furthermore, we improve a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 58 publications
(73 reference statements)
0
7
0
Order By: Relevance
“…After writing the final version of the manuscript [19] Hamada turned attention 1 to the arxiv paper [7]. In [7], the authors generalize the classical Schwarz lemmas of planar harmonic mappings into the sharp forms for Banach spaces, and present some applications to sharp boundary Schwarz type lemmas for pluriharmonic mappings in Banach spaces. Recently, Hamada and Kohr published paper [12], where authors discussed rigidity theorems on the boundary for holomorphic mappings.…”
Section: Schwarz Lemma and Hilbert Spacesmentioning
confidence: 99%
See 4 more Smart Citations
“…After writing the final version of the manuscript [19] Hamada turned attention 1 to the arxiv paper [7]. In [7], the authors generalize the classical Schwarz lemmas of planar harmonic mappings into the sharp forms for Banach spaces, and present some applications to sharp boundary Schwarz type lemmas for pluriharmonic mappings in Banach spaces. Recently, Hamada and Kohr published paper [12], where authors discussed rigidity theorems on the boundary for holomorphic mappings.…”
Section: Schwarz Lemma and Hilbert Spacesmentioning
confidence: 99%
“…In the Section 2 we will improve this estimate. Next S. Chen, H. Hamada, S. Ponnusamy, R. Vijayakumar in [7] observed that using [ [11], Proposition 1.8] and the arguments similar to those in the proof of their Theorem 3.3 [7] one can obtain a better estimate:…”
Section: Schwarz Lemma and Hilbert Spacesmentioning
confidence: 99%
See 3 more Smart Citations